Does the Stock Market Gender Stereotype Corporate Boards? Evidence from the Market's Reaction to Directors' Trades. (30th January 2012) - Gregory, Alan; Jeanes, Emma; Tharyan, Rajesh; Tonks, Ian
<x xml:space="preserve">Abstract</x> Attitudes towards male and female managers within organizations are well documented, but how the stock market perceives their relative capabilities is less studied. Recent evidence documents a negative short‐run market reaction to the appointment of female chief executive officers and suggests that female executives are less informed than their male counterparts about future corporate performance. These results appear to dispute the stock market value of having women on corporate boards. However, such short‐run market reactions may retain a 'gender bias', reflecting the prevalence of negative stereotypes, where the market reacts to 'beliefs' rather than 'performance'. This study tests for such bias by examining the stock market reaction to directors' trades in their own companies' shares, by measuring both the short‐run and longer‐term returns after the directors' trades. Allowing for firm and trade effects, some evidence is found that, in the longer term, markets recognize that female executives' trades are informative about future corporate performance, although initially markets underestimate these effects. This has important implications for research that has attempted to assess the value of board diversity by examining only short‐run stock market responses.